Historical and Diplomatic Relations of India with Saudia Arabia and Iran - Youns, Eman; Muzaffar, Muhammad (Annals of Human and Social Sciences, 2025)
Abstract The aim of this study is to explore the historical and diplomatic relations of India with Saudi Arabia and Iran. Using a qualitative research approach, the study examines key periods of engagement, cultural exchanges, economic partnerships, and political collaborations between India and these two significant Middle Eastern nations. The findings reveal that India’s relations with Saudi Arabia and Iran have been shaped by a combination of historical ties, shared economic interests, religious connections, and evolving geopolitical dynamics. This study contributes to a deeper understanding of how past interactions continue to influence contemporary diplomacy and foreign policy strategies. It is recommended to restore and reinforce attaches with Saudi Arabia, Pakistan should put a serious need on fundamental obligation and can be achieved with the help of basic level visits, social trades, and joint drives that feature shared interests, especially in regions like counter-mental battling, exchange, and hypothesis.